2021
DOI: 10.3390/plants10112540
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glycine Betaine (Natural and Synthetic) on Growth, Metabolism and Yield Production of Drought-Stressed Maize (Zea mays L.) Plants

Abstract: A study was carried out to evaluate the effectiveness of sugar beet extract (SBE) and glycine betaine (GB) in mitigating the adverse effects of drought stress on two maize cultivars. Seeds (caryopses) of two maize cultivars, Sadaf (drought-tolerant) and Sultan (drought-sensitive) were sown in plastic pots. Plants were subjected to different (100%, 75% and 60% field capacity (FC)) water regimes. Then, different levels of SBE (3% and 4%) and GB (3.65 and 3.84 g/L) were applied as a foliar spray after 30 days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 72 publications
(79 reference statements)
4
16
0
Order By: Relevance
“…Phenolics are part of the low-molecular antioxidant defense system implicated as an ROS scavenger [ 3 , 40 ]. In general, drought stress led to the induction of phenolic compounds [ 33 , 38 , 41 , 42 ], which is in line with our data observed for wheat. The opposite results found for maize could be related to species specific differences.…”
Section: Discussionsupporting
confidence: 91%
“…Phenolics are part of the low-molecular antioxidant defense system implicated as an ROS scavenger [ 3 , 40 ]. In general, drought stress led to the induction of phenolic compounds [ 33 , 38 , 41 , 42 ], which is in line with our data observed for wheat. The opposite results found for maize could be related to species specific differences.…”
Section: Discussionsupporting
confidence: 91%
“…Soil water deficit during the sensitive growth, blooming, flowering, and fruiting stages, can affect plant growth and yield (Abdel-Kader et al, 2015;Eid et al, 2022). This study showed that exogenous foliar supplementation with GB, proline, and chitosan could maintain the level of cotton yield components under DIW conditions, with GB application generating the strongest enhancement effects on cotton yield components, which was consistent with previously reported trends (Bhuiyan et al, 2019;Hamani et al, 2021;Shafiq et al, 2021). In addition, exogenous GB application enhanced plant growth and yield qualities, Chls, osmolyte concentration, total phenolics, ascorbic acid, and the activities of ROS scavenging enzymes, including SOD, peroxidase, and CAT, but decreased the leaf relative membrane permeability and malondialdehyde (MDA) concentration (Shafiq et al, 2021;Hamani et al, 2021).…”
Section: Effects Of Irrigation Intervals Drought Tolerance Inducers A...supporting
confidence: 92%
“…Similarly, foliar-applied GB in rapeseed was shown to improve the chlorophyll concentration under DIW conditions . The enhanced pigment concentrations is likely due to the role of GB and proline in protecting the photosynthetic apparatus, stabilizing the Rubisco structures, as well as plant cell membranes under DIW (Hamani et al, 2021;Shafiq et al, 2021). Moreover, GB has been demonstrated to improve the efficiency of photosynthetic machinery (Hamani et al, 2021;Shafiq et al, 2021)…”
Section: Effects Of Irrigation Intervals Drought Tolerance Inducers A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The POD activities of 1–5 in Group A were similar to that of CK 2 , which showed that the POD activity of cucumber under salt stress did not increase due to AM-zein. The decrease in POD activity resulted in a large number of ROS, which could not be timely decomposed [ 52 ]. A large number of ROS attacked the lipid membrane of cucumber cells, resulting in a large amount of material flow from the cells and the cucumber cell growth was adversely affected.…”
Section: Resistance Of Cucumber To Salt Stressmentioning
confidence: 99%